The Zoogeography of Marine Tardigrada - Kaczmarek, Łukasz; Bartels, Paul J.; Roszkowska, Milena; Nelson, Diane R. (Zootaxa, 2015)
This monograph describes the global records of marine water bears (Phylum Tardigrada). We provide a comprehensive list of marine tardigrades recorded from around the world, providing an up-to-date taxonomy and a complete bibliography accompanied by geographic co-ordinates, habitat, substrate and biogeographic comments. A link is provided to an on-line interactive map where all occurrences for each species are shown. In total we list 197 taxa and their 2240 records from 39 oceans and seas and 18 Major Fishing Areas (FAO). It is hoped this work will serve as a reference point and background for further zoogeographic and taxonomic studies on marine tardigrades.